Molecular Simulation Techniques in Protein-Drug Interactions for Neurodegenerative Diseases - Mohammed, Mohammed Nooruldeen; Hussein Ali, Abdullah; Mohammed, Aqel Jasim (American Journal of Botany and Bioengineering, 2025)
Neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s continue to pose major global health challenges, with treatment efficacy remaining limited. Although protein-drug interactions are central to therapeutic development, current experimental methods often lack the resolution to capture dynamic molecular behaviors. This study explores advanced molecular simulation techniques—including molecular dynamics (MD), Monte Carlo simulations, docking methods, and free energy calculations—to investigate protein-drug interactions at atomic precision. These simulations provide critical insights into protein folding, binding affinities, and aggregation behaviors associated with neurodegeneration. By simulating complex molecular systems and drug-target interactions, the study underscores the potential of computational modeling to enhance drug discovery pipelines, optimize therapeutic targeting, and contribute to the development of personalized medicine in neurology.